1999
DOI: 10.1111/j.2042-3306.1999.tb03854.x
|View full text |Cite
|
Sign up to set email alerts
|

Encephalopathy with idiopathic hyperammonaemia and Alzheimer type II astrocytes in Equidae

Abstract: Summary In 3 mature female horses of varying breeds, episodes of colic and depression for 1–4 days preceded an encephalopathic disorder with maniacal behaviour, anxiety, profuse sweating and, in one case, terminal opisthotonus. Blood ammonia levels were elevated approximately 10‐fold. At necropsy, there were gastrointestinal serosal and mesenteric haemorrhages. Histologically, all 3 cases revealed diffuse Alzheimer type II astrocytes in the cerebral grey matter. Alzheimer type II astrocytes were glial fibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 20 publications
3
35
0
4
Order By: Relevance
“…The neurologic signs reported in this study are consistent with those previously reported in llamas diagnosed with hepatic lipidosis 17 and suspected to be associated with hepatic encephalopathy in horses, 10 cattle, 4 and sheep.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The neurologic signs reported in this study are consistent with those previously reported in llamas diagnosed with hepatic lipidosis 17 and suspected to be associated with hepatic encephalopathy in horses, 10 cattle, 4 and sheep.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings are consistent with staining patterns for glial fibrillary acid protein and S100 protein reported in horses with idiopathic hyperammonemia. 10 Additional studies including serum blood ammonia levels and more thorough and systematic examination of brain sections would potentially allow for statistical evaluation of lesion predominance and distribution and for correlations among signalment, clinical signs, biochemical abnormalities, underlying disease, and histopathologic lesions. Transmission electron microscopy and development of an immunohistochemical protocol for glutamate synthetase in llamas may allow for confirmation of glutamine accumulation within llama Alzheimer type II cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similar cases of hyperammonemia of unknown origin have also been described in humans and dogs. [12][13][14][15][16] Several similarities between the horse reported in this study and other equine patients were found with regard to history, clinical findings, and laboratory abnormalities. A postmortem examination was performed on 4 of the previously reported horses and showed similar findings.…”
mentioning
confidence: 68%
“…To the authors' knowledge, 7 similar cases of equine idiopathic hyperammonemia have been reported in the relevant veterinary literature to date. 1,11,12 These cases were thought to be associated with possible gastrointestinal disorders resulting in hyperammonemia without marked evidence of liver disease. Similar cases of hyperammonemia of unknown origin have also been described in humans and dogs.…”
mentioning
confidence: 99%
“…Auch sind idiopathische Hyperammoniämien beschrieben, welche ev. in Zusammenhang mit einer Clostridieninfektion stehen (Hasel et al 1999, Wilkins et al 2003. Symptome weisen auf eine Beeinträchti-gung der Grosshirnfunktion hin und beinhalten progressive Apathie, Somnolenz oder Stupor, Kreiswandern und Kopfpressen.…”
Section: Hyperammoniämieunclassified